Perspektif Model TAM Dalam Adaptasi Pembelajaran Akuntansi Melalui E-Learning Selama Pandemi COVID-19 - Ira Setiawati; Paulus Th. Basuki Hadiprajitno; Muhammad Noor Ardiansah (Universitas Katolik Soegijapranata Semarang, 2021)
This study aims to analyze students' intention to do online-accounting learning during the Covid-19 pandemic by adapting the Technology Acceptance Model (TAM) model. Testing the TAM model during a pandemic in the Indonesia context is expected to reveal the determinants of behavior in online accounting learning, which requires a comprehensive acknowledgment of knowledge, skills, and attitude, directly affected during a pandemic. The population is accounting students in Central Java, who were given an online questionnaire. A sample of 766 data was analyzed with the equation model structure (SEM) using WrapPLS. The results show that Perceived Ease of Use, Perceived Usefulness has a significant effect on E-Learning Actual Usage mediated by the Behavior Intention variable. These results further strengthen the TAM model in the context of the Covid-19 pandemic.